Extension Activities in the Fashion Design Program: Opportunities for the World of Work (Revista de Ensino em Artes, Moda e Design, 2026)
This study aims to analyze the opportunities that arise from extension activities in the Fashion Design program at the Federal Institute of Piauí, Piripiri campus. The methodology adopted follows a qualitative approach, based on bibliographic, documentary, and descriptive research. For this study, we relied on Fontenele (2024), Imperatore (2018), Betta (2018), Ciavatta (2012), among others. Through the experiences gained in the extension projects developed in the Fashion Design program, from its implementation to the present day, the importance of the formative process is promoted through the tripod: Teaching, Research, and Extension, culminating in inclusion in the world of work. Therefore, this study cannot be considered finished, as there are still possibilities for further development and new discussions on the topic. Nevertheless, it aims to encourage extension practices in higher education in Brazil as a tool for social transformation.
Keywords: extension projects; higher education; opportunities; world of work